Back to the future? Late Holocene marine food web structure in a warm climatic phase as a predictor of trophodynamics in a warmer South‐Western Atlantic Ocean. (12th December 2018) - Bas, Maria; Briz i Godino, Ivan; Álvarez, Myrian; Vales, Damián G.; Crespo, Enrique A.; Cardona, Luis
Abstract: Stable carbon and nitrogen isotope ratios in the skeletal elements of both ancient and modern marine species from the Beagle Channel were used to compare the structure of Late Holocene and modern food webs, and predict potential changes as a result of a Sea Surface Temperature (SST) increase in the region. Complementary, ancient and modern shells of limpets and mussels were isotopically analysed to explore changes in the isotopic baseline and compare marine food webs through time after an appropriate correction for baseline shifts. Results confirmed a declining pattern of marine primary productivity during the Late Holocene in the Beagle Channel. In general, the isotopic niches overlapped largely in the ancient food web in comparison to the current marine one, with the exception of that of cormorants ( Phalacrocorax sp.). Our data suggest that all the species that have undergone intense human exploitation ( Arctocephalus australis, Otaria flavescens and Merluccius sp.) significantly increased their trophic levels. The most important finding of this work was the very high isotopic overlap between snoek ( Thyrsites atun ) and hake ( Merluccius sp.) during the Late Holocene. Increasing SST as a result of global warming could favour the recolonization of the southern South‐Western Atlantic Ocean by snoek from the South‐Eastern Pacific Ocean, with a potential impact on the landings of the economically important Argentine and Austral hake. These findings highlight the relevance of using zooarchaeological remains for providing predictions about marine food webs changes in the near future. Abstract : The most important finding of this work is the high trophic overlap between snoek and hake during the Late Holocene. Furthermore, all the species that have undergone intense human exploitation significantly increased their trophic levels. Finally, increasing Sea Surface Temperature (SST) could favour the recolonization of the southern South‐Western Atlantic Ocean by snoek, with a likely impact on the population of hake.